2013
DOI: 10.1080/01457632.2013.812491
|View full text |Cite
|
Sign up to set email alerts
|

Flow Boiling Pressure Drop of R134a in Microdiameter Tubes: Experimental Results and Assessment of Correlations

Abstract: The experimental results of two phase flow boiling pressure drop of R134a in vertical micro diameter stainless steel tubes are presented in this paper. The tests were conducted using four tubes; one tube with an inner diameter of 0.52 mm and 100 mm heated length and three tubes with an inner diameter of 1.1 mm and different heated lengths (150, 300 and 450 mm). Other experimental conditions include: mass flux range of 200-500 kg/m 2 s, system pressure range of 6-10 bar, inlet sub-cooling of about 5K and heat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Accordingly, Song et al [37] appraised twenty nine pressure drop correlations and reported that the best performing relation was able to predict the results within error band of ±30%. Similar conclusions were also drawn in other studies [38][39][40][41]. Indeed, based on the above-mentioned investigations, having the ability to predict the data in the error range of ±30% seems to be satisfactory in two-phase flow regimes.…”
Section: Pressure Drops Of the Smooth Tubesupporting
confidence: 88%
“…Accordingly, Song et al [37] appraised twenty nine pressure drop correlations and reported that the best performing relation was able to predict the results within error band of ±30%. Similar conclusions were also drawn in other studies [38][39][40][41]. Indeed, based on the above-mentioned investigations, having the ability to predict the data in the error range of ±30% seems to be satisfactory in two-phase flow regimes.…”
Section: Pressure Drops Of the Smooth Tubesupporting
confidence: 88%
“…They reported that the flow boiling pressure drop increased with increasing mass flux and heat flux. The effect of system pressure on the flow boiling pressure drop was also studied in the literature [5,9,12]. Tran et al [9] carried out sets of experiments in two microtubes (D = 2.46 mm and 2.92 mm) and one rectangular microchannel (Dh = 2.4 mm) using various working fluids (R-134a, R-113 and R-12).…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the flow boiling pressure drop increased with decreasing system pressure in all experiments. In another study, Mahmoud et al [12] tested four microtubes with one tube with an inner diameter of 0.52 mm and 100 mm heated length and three tubes with an inner diameter of 1.1 mm and different heated lengths (150, 300, and 450 mm) using R-134a. They concluded that the flow boiling pressure drop increased with decreasing system pressure due to the reduction of the liquid vapour density ratio.…”
Section: Introductionmentioning
confidence: 99%